2002
DOI: 10.1128/iai.70.7.3656-3664.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Helminth Infection Induces Alternatively Activated Macrophages Expressing High Levels of CCR5 with Low Interleukin-12 Production and Th2-Biasing Ability

Abstract: Helminth infections induce Th2-type biased immune responses. Although the mechanisms involved in this phenomenonare not yet clearly defined, antigen-presenting cells (APC) could play an important role in this process. Here, we have used peritoneal macrophages (F4/80؉) recruited at different times after challenge with Taenia crassiceps as APC and tested their ability to regulate Th1/Th2 differentiation. Macrophages from acute infections produced high levels of interleukin-12 (IL-12) and nitric oxide (NO), paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(146 citation statements)
references
References 49 publications
(63 reference statements)
9
135
0
2
Order By: Relevance
“…These have been shown to suppress proliferation of Ag-specific T cells through a contact-dependent mechanism (58). However, alternatively activated macrophages do not develop in filarial-infected IL-4R Ϫ/Ϫ mice (J. E. Allen, unpublished observation), or in STAT6-deficient animals infected with other helminths (59,60). By showing that B. malayi induces Foxp3 within the T cell population even in the absence of IL-4R signaling, we have established that this process is independent of alternatively activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These have been shown to suppress proliferation of Ag-specific T cells through a contact-dependent mechanism (58). However, alternatively activated macrophages do not develop in filarial-infected IL-4R Ϫ/Ϫ mice (J. E. Allen, unpublished observation), or in STAT6-deficient animals infected with other helminths (59,60). By showing that B. malayi induces Foxp3 within the T cell population even in the absence of IL-4R signaling, we have established that this process is independent of alternatively activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…AAMΦs are observed in a variety of helminth infections, including Th2-type immune responses to Schistosoma mansoni [2], Heligmosomoides polygyrus [3], Nippostrongylus brasiliensis [4], Taenia crassiceps [5], Trichinella spiralis [6], Fasciola hepatica [7], Ascaris suum [8], and filarial parasites [9]. A number of markers are used to identify AAMΦs ( Figure 1).…”
Section: Characterization and Phenotypementioning
confidence: 99%
“…9 It has been suggested that antigen-presenting cells (APCs) play a crucial role in the skewing of Th1 and Th2 differentiation. 10,11 IL-12 is a heterodimeric cytokine composed of p40 and p35 which strongly promotes the differentiation of naive CD4 ϩ T cells to the Th1 phenotype and suppresses the synthesis of Th2-type cytokines. 12 IL-12 is produced primarily by APCs and the production is regulated by IL-10 and IFN-␥.…”
mentioning
confidence: 99%